2014
DOI: 10.1111/tct.12052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating PLATO: postgraduate teaching and learning online

Abstract: PLATO supports education and helps deliver UK General Medical Council standards. Future plans should address the suggested recommendations to realise cost savings for NHS Wales and the Wales Deanery. The findings have wider applicability to others developing or using VLEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…We also found that the self-assessment questions relating to the skills required to care for women or couples with vulvodynia improved after WBE compared to baseline. The majority of previous WBE studies measured only a change in knowledge and/or the attitude towards a subject of education (Durkin, 2008;Eaton-Spiva and Day, 2011;Brown and Bullock, 2014). However, some studies found that it was possible to adopt new knowledge acquired from WBE and to transfer this knowledge to practice (Hart et al, 2008;Feng et al, 2013;Lahti et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the self-assessment questions relating to the skills required to care for women or couples with vulvodynia improved after WBE compared to baseline. The majority of previous WBE studies measured only a change in knowledge and/or the attitude towards a subject of education (Durkin, 2008;Eaton-Spiva and Day, 2011;Brown and Bullock, 2014). However, some studies found that it was possible to adopt new knowledge acquired from WBE and to transfer this knowledge to practice (Hart et al, 2008;Feng et al, 2013;Lahti et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Web-based education (WBE) is a cost-effective way of educating large numbers of healthcare providers, in terms of travel costs, as well as personnel time and trainer costs, enabling them to deliver the same consistent programme (Cook et al, 2010;Brown and Bullock, 2014;Lahti et al, 2014a). Well-designed WBE is also a dynamic, innovative and rich method of providing nursing staff with education on specific topics.…”
Section: Web-based Educationmentioning
confidence: 99%
“…The complete web-based training and certification program will be hosted in a Moodle virtual learning environment (Moodle Pty Ltd, West Perth, WA, Australia), a commonly used shareware software within online medical training [10,11,23]. However, Moodle was not used as the platform for this pilot project due to restricted time.…”
Section: Web-based Training and Certification Programmentioning
confidence: 99%
“…E-learning has already proven to be a valuable asset when increasing the competencies of health professionals, in both industrial and developing countries [8][9][10][11][12][13], and has been proliferating until now with the purpose of medical education at universities, as a counteraction to traditional classroom teachings [14]. It has proven to be a useful tool when harmonizing teachings that are aimed worldwide, across different languages and clinical settings, and has been used with great progress in resource-constrained countries [15].…”
Section: Introductionmentioning
confidence: 99%
“…In more recent times, CPD and CME have extended to online learning and teaching. 5 Not only is this mode of access and delivery relevant to contemporary society and practice, but it is also especially useful to doctors in non-metropolitan areas.…”
mentioning
confidence: 99%